(untitled) (Clinics, 2012)
OBJECTIVE: The aim of this study was to compare female sexual function after surgical treatment of anterior vaginal prolapse with either small intestine submucosa grafting or traditional colporrhaphy. METHODS: Subjects were randomly assigned, preoperatively, to the small intestine submucosa graft (n = 29) or traditional colporrhaphy (n = 27) treatment group. Postoperative outcomes were analyzed at 12 months. The Female Sexual Function Index questionnaire was used to assess sexual function. Data were compared with independent samples or a paired Student's t-test. RESULTS: In the small intestine submucosa group, the total mean Female Sexual Function Index score increased from 15.5±7.2 to 24.4±7.5 (p